How fast and how well the Omicron epidemic was curtailed. A Guangzhou experience to share - Cai, Wenfeng; Yang, Zifeng; Liang, Jingyi; Lin, Zhengshi; Ma, Yu; Chen, Chun; Li, Yan; Li, Yongming; Mai, Zhitong; Mai, Kailin; Kong, Xuetao; Liang, Xingyi; et al. (Frontiers in Public Health, 2022)
On April 07, 2022, an epidemic caused by SARS-CoV-2 Omicron (BA.2) variant broke out in Guangzhou, China, one of the largest transportation and logistical hubs of the country. The first case was identified unexpectedly in a school routine nucleic acid screening test and fast, strict epidemic control measures were implemented subsequently. Transmission characteristics of Omicron variant were analyzed for 273 confirmed cases and key places involved in this epidemic were fully presented. The median incubation time and generation time were also 3.00 days, and the reproduction number Rt was sharply increased with a peak of 4.20 within 2 days. We tried all-out effort to tackle epidemic in key places, and the proportion of confirmed cases increased from 61.17% at stage 2 to 88.89% at stage 4. Through delimitated-risk area management, 99 cases were found and the cases were isolated in advance for 2.61±2.76 days in lockdown zone, 0.44±1.08 days in controlled zone, and 0.27± 0.62 days in precautionary zone. People assigned with yellow code accounted for 30.32% (84/277) of confirmed COVID-19 cases and 83.33% of them were detected positive over 3 days since code assignment. For the districts outsides the epi-center, the implementation duration of NPIs was much shorter compared with the Delta epidemic last year. By blocking out transmission risks and adjusting measures to local epidemic conditions through all-out effort to tackle epidemic in key places, delimitated-risk area management, and health code management of at-risk population, the Guangzhou Omicron epidemic was contained within 18 days.